2017
DOI: 10.1111/josh.12540
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of School‐Based Health Centers for Human Papillomavirus Vaccination Visits: A Mixed‐Methods Study

Abstract: BACKGROUND Countries with high human papillomavirus (HPV) vaccination rates have achieved this success largely through school-based vaccination. Using school-based health centers (SBHCs) in the US, where HPV vaccine remains underutilized, could improve uptake. In this mixed-methods study, we examined acceptability, facilitators, and barriers of HPV vaccination visits at SBHCs from the perspectives of adolescents and parents. METHODS We conducted qualitative interviews and structured surveys with adolescents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Therefore, collaborating with nongovernmental health organizations and universities could be a feasible direction for school-based HPV vaccination programs in the future. Furthermore, school-based health centers in the United States were reported to improve HPV vaccine uptake among adolescents because they offer convenience and do not affect school or work [40]. Despite the lack of school-based health centers in primary and secondary schools in Hong Kong, with the support of the literature indicating school-based format can enhance vaccination motivation [37, 4043] and offer trust to parents [44], the home-school-doctor model could be considered an alternative in the implementation of school-based HPV vaccination programs [16] in the future to improve vaccine uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, collaborating with nongovernmental health organizations and universities could be a feasible direction for school-based HPV vaccination programs in the future. Furthermore, school-based health centers in the United States were reported to improve HPV vaccine uptake among adolescents because they offer convenience and do not affect school or work [40]. Despite the lack of school-based health centers in primary and secondary schools in Hong Kong, with the support of the literature indicating school-based format can enhance vaccination motivation [37, 4043] and offer trust to parents [44], the home-school-doctor model could be considered an alternative in the implementation of school-based HPV vaccination programs [16] in the future to improve vaccine uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Pandemic-related challenges such as limited catch-up appointments in the clinics were also noted. School-based interventions may address the logistical barriers in communities where the social needs are greater [ 60 ]. For example, others have found that parents who struggle to take off work and uninsured parents are more willing to partake in school-based vaccination programs [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Countries that have achieved high rates (>70%) of HPV vaccine series completion, such as England and Australia, have largely accomplished this through school-based vaccination programs. [40][41][42][43] In the United States, parents generally have favorable opinions of offering the HPV vaccine at SBHCs 44 although with only 2000 SBHCs in the country 39 most children do not have access to a SBHC. Findings from our study support this claim-with only 12% of our school nurses reporting that they are based in a SBHC.…”
Section: Discussionmentioning
confidence: 99%